Syncopal patients without prodromes exhibit a diverse pattern of adenosine release during head-up tilt test. (3rd October 2022) - Fragakis, N; Antoniadis, A; Sotiriadou, M; Virgiliou, C; Ballauri, I; Gika, H; Boulmpou, A; Triantafyllou, K; Vergopoulos, S; Bakogiannis, C; Papadopoulos, C; Tzikas, S; et al.
Abstract: Background/Introduction: In a significant proportion of patients with neurally-mediated syncope (NMS), the mechanism of syncope remains largely undetermined. Adenosine has been proposed as a central humoral factor in various forms of NMS: high Adenosine Plasma Levels (ADP) are encountered in patients with vasovagal syncope (VVS), low ADP in non-prodromes syncope (NPS), while ADP in patients with situational syncope SS are less well determined. Purpose: We sought to assess ADP in patients with different clinical forms of syncope, with an emphasis on the presence or absence of prodromal symptoms, as well as the relation between ADP and the outcomes of Head-Up Tilt Table Test (HUTT) and Adenosine test (ADT). Methods: Patients with different clinical types of NMS (n=124), i.e., VVS, NPS, or SS, were investigated using a standard protocol including HUTT and ADT. During HUTT, ADP was measured in the supine position, at table tilting, and in syncope. Results: Baseline ADP did not differ among groups. ADP at syncope were higher in NPS compared to VVS (1.55±1.29 vs 0.16±0.05 μM, p=0.03) and SS (0.15±0.05 μM, p=0.02). In NPS, ADP increased from the supine position to the time of syncope (0.47±0.25 to 1.55±1.29 μM, p=0.04). In VVS, ADP increased only from the supine to the tilt position (0.23±0.04 to 0.35±0.10 μMu, p=0.02), while in SS ADP did not change in any stage of HUTT. SS was associated with cardioinhibitory HUTT (OR 3.40, 95% CI 1.05 to 9.56, p=0.04) and positive ADT (OR 4.22, 95% CI 1.47 to 11.46, p=0.012). Conclusion(s): A distinct pattern of ADP increase is noted during HUTT in NPS, suggesting that an excessive increase of ADP may play the key role in triggering this type of clinical presentation of syncope independently of the baseline ADP. Cardioinhibition prevails in patients with SS without clear adenosine involvement. Such observations contribute to an enhanced understanding of the pathophysiology of different clinical forms of syncope which may offer the possibility to tailor the management approach appropriately. Funding Acknowledgement: Type of funding sources: None.